Construction and count of multi-output rotation symmetric resilient functions with 8 input variables - Jiao DU; Yu-jing SHANG; Jin-ling ZHAO; Le DONG; En ZHANG (Tongxin xuebao)
The value ranges of the number of output variables were determined respectively under the existence of multi-output rotation symmetric balanced functions and resilient functions with 2rinput variables.Based on the equivalence between the resilient functions and large sets of orthogonal arrays,some results on the construction and count of multi-output rotation symmetric balanced functions with 8 input variables were presented according to the different dimensions of output vectors,and construction and count of multi-output rotation symmetric 1-resilient functions with 8 input variables were also studied.Besides,constructions of multi-output rotation symmetric resilient functions are transformed into the problem of solving a system of equations.